Effect of rumen-specific live yeast supplementation on in situ ruminal degradation of forages differing in nutritive quality - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2019.